Effects of supercritical CO₂/water imbibition under dynamic pressures on shale mechanics and acoustic emission characteristics. (1st August 2022) - Lyu, Qiao; Wang, Kaixi; Hu, Chenger; Shi, Jindong; Tan, Jingqiang; Zhang, Guanglei; Chen, Shefa; Ranjith, P.G.
Highlights: The effects of supercritical CO2 and water immersion on the mechanical properties of shale under different dynamic pressures are investigated. The strength and Young's modulus of shale are decreased more significantly after water immersion compared to supercritical CO2 immersion. Compared with the constant pressure imbibition, the dynamic pressure imbibition changes the microstructure of shale and weakens its mechanical properties more significantly. Abstract: During exploitation of shale gas and geological sequestration of CO2 in shale gas reservoirs, the temperature and pressure of shale are increased with depth, whereas the reservoir pressure is gradually decreased with depth as exploitation proceeds. Therefore, it is important to investigate the effects of CO2 and water on the mechanical properties of shale under dynamic pressure conditions. In this study, we have investigated the effects of supercritical CO2 and water immersion on the mechanical properties of shale under different dynamic pressures (pressure 1: 20–8 MPa; pressure 2: 40–28 MPa), respectively. The test results indicate that after soaking in supercritical CO2 and water, the uniaxial compressive strength (UCS) of shale is decreased by 51.05% and 58.36% (pressure 1), and by 35.98% and 36.84% (pressure 2), respectively. The strength and Young's modulus of shale are decreased more significantly after water immersion compared to supercritical CO2 immersion. Due to the matrix compression effects, the mechanical properties of shale are changed more significant under lower imbibition pressures. Supercritical CO2 immersion leads to increase in the Poisson's ratio along with more complex fracture patterns, whereas water immersion results in slight decrease in the Poisson's ratio along with shear fractures only. The acoustic emission (AE) signals have obvious stage characteristics during the compressional deformation of samples, and the AE energy is mainly generated in the unstable crack propagation stage. Supercritical CO2 immersion plays an important role in crack generation, whereas water immersion is dominated by the alteration of pore structure. Compared with the constant pressure imbibition, the dynamic pressure imbibition changes the microstructure of shale and weakens its mechanical properties more significantly. The results of this study may help to better evaluate the effects of CO2 and water on the mechanical properties of shale during exploitation of shale gas.